TOLERANCE AND MIGRATION - V. V. Tuzov (Дискурс, 2016)
Tolerance has contradictory essence. Its application to the process of migration has limitations. Limitations are related to quality of relations of capitalist society. This quality is competition. Tolerant attitude of the receiving party toward guests without good attitude of guests toward the host party is dangerous